2020
DOI: 10.29252/rme.12.2.10
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Clinical Self-Efficacy and Academic Achievement Motivation in Nursing Students

Abstract: Introduction: Self-efficacy and academic achievement motivation are two key factors in the process of clinical nursing education. The purpose of this study was to determine the relationship between clinical self-efficacy and academic achievement motivation in nursing students Schools of Nursing in East Gilan. Methods: This descriptive-correlational study was conducted on 105 fourth year nursing students of East Guilan Nursing Universities in 2017.The method was cluster random sampling. Data collection tools we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Motahari et al reported that 98% of senior nursing students had high and moderate SECP scores. They showed that the highest score belonged to the implementation area, and the lowest was related to diagnosis and planning (26). Other studies also showed a high SECP of nursing students (27,28), which is not consistent with the results of the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Motahari et al reported that 98% of senior nursing students had high and moderate SECP scores. They showed that the highest score belonged to the implementation area, and the lowest was related to diagnosis and planning (26). Other studies also showed a high SECP of nursing students (27,28), which is not consistent with the results of the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Te results showed that CSE.C has a signifcant statistically relationship with the marital status. In Motahari et al's study, married students had higher clinical self-efcacy than unmarried students, which is not consistent with the results of the present study [20]. Te fndings of Asadpour and Sadat Hosseini's study showed that normal women and men have higher self-efcacy compared to divorced people [21], which is not consistent with the results of the present study.…”
Section: Comparison Between Csec and Jsc Scores Amongcontrasting
confidence: 97%
“…The results also indicated that clinical self-efficacy was at an average level in the majority of research units, which is consistent with the findings of Salimi et al [ 34 ]. Inconsistent with these results, the findings of some studies have indicated that students had a high level of self-efficacy [ 17 , 35 , 36 ], although Zhang et al reported the level of self-efficacy of Chinese students as low [ 37 ]. Considering the many factors affecting the self-efficacy of nursing students such as academic semester, type of education and clinical training, achieving different results of self-efficacy levels in different studies is predictable and inevitable [ 17 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 94%